Clinical and Biomechanical Effects of Femoral Neck Buttress Plate used for Vertical Femoral Neck Fractures. Issue 3 (March 2022) - Steffensmeier, Andrew; Shah, Nihar; Archdeacon, Michael; Watson, David; Sanders, Roy W; Sagi, Henry C
Highlights: FNBP does not appear to significantly impact union, femoral neck shortening or changes in neck shaft angle when used as an adjunct in the treatment of vertical femoral neck fractures. FNBP may be beneficial during reduction and initial fixation of vertical femoral neck fractures. Vertical femoral neck fractures in young patients are due to high energy trauma and can be very difficult to treat. Abstract: Purpose: To investigate both the biomechanical and clinical effect of an inferomedial femoral neck buttress plate (FNBP) used to augment a sliding hip screw (SHS) and anti-rotational screw (ARS) in the treatment of traumatic vertical femoral neck fractures. Methods: Part 1: Clinical - Retrospective review of patients under age 65 treated with open reduction of a vertical femoral neck fracture. Patients were divided into two groups: Group 1 patients (18 patients) had SHS/ARS fixation augmented with a FNBP, while Group 2 patients (18 patients) had SHS/ARS fixation alone and were matched for age and sex. Demographic data, OTA fracture classification, immediate post-operative and follow-up radiographs were analyzed for quality of reduction, femoral neck shortening (FNS), neck-shaft angle (NSA), avascular necrosis (AVN) and union. Part 2: Biomechanical - Pauwels III femoral neck osteotomy was created in five pairs of cadaveric specimens, then each fracture was reduced and stabilized with a SHS/ARS construct. Specimens were matched and split into Groups 1 and 2, similar to Part 1. Cadaveric specimens were axially loaded in cyclical fashion to analyze for construct stiffness, fracture displacement femoral neck shortening and changes in the neck shaft angle. Results: Part 1: There were 18 matched patients (14 males and 4 females) in both Group 1 and Group 2. There were no statistically significant differences between the two groups with respect to Pauwels angle, femoral neck shortening, changes in neck-shaft angle, AVN or nonunion. One reoperation in Group 1 and four in Group 2. Part 2: All five cadaveric specimens in both groups survived the 10, 000-cycle loading regimen. We were unable to detect any significant differences between the two groups with respect to construct stiffness, change in neck-shaft angle or amount of femoral neck shortening. Conclusion: Based on the results of both clinical case series and biomechanical testing, an inferomedial neck buttress plate does not appear to offer long-term benefits with respect to maintenance of alignment or achieving union but may potentially help in obtaining the reduction.